2021
DOI: 10.1371/journal.pone.0249888
|View full text |Cite
|
Sign up to set email alerts
|

Aetiology of acute diarrhoea in children in Shanghai, 2015–2018

Abstract: Diarrhoea remains a major cause of childhood morbidity and mortality worldwide. This study aimed to monitor the aetiology of acute diarrhoea in children in Shanghai. Paediatric outpatients with acute diarrhoea were enrolled in the study from Jan 2015 to Dec 2018. Faecal samples were collected for testing. Enteric bacteria were identified and typed by culture and serotyping, respectively. Enteric viruses were identified by real-time PCR. Enteric pathogens were identified in 1572 (58.4%) of the 2692 enrolled chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
4
9
0
Order By: Relevance
“…Rotavirus A was frequently associated with viral diarrhea in children. This result was similar to previous studies 9,13 . Inhibiting rotavirus disease is a national and global priority.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Rotavirus A was frequently associated with viral diarrhea in children. This result was similar to previous studies 9,13 . Inhibiting rotavirus disease is a national and global priority.…”
Section: Discussionsupporting
confidence: 92%
“…This result was similar to previous studies. 9,13 Inhibiting rotavirus disease is a national and global priority. And considering that the primary virus causing diarrhea in children almost worldwide is still rotavirus, 14 we still strongly recommend the inclusion of rotavirus vaccine in the national immunization program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotavirus and calicivirus were the predominant viral agents. This result was similar to previous studies [9,13]. It's worth noting that the number of cases of rotavirus had a downtrend but the calicivirus had an upward trend.…”
Section: Discussionsupporting
confidence: 91%
“…A large national-based AGE surveillance study conducted in China between 2009 and 2018 revealed norovirus and rotavirus as the leading agents detected in patients aged <5 years, and norovirus was detected in 32.2% of 58,620 analyzed samples [ 35 ]. Other studies performed elsewhere have found norovirus prevalence varying from 15% to 21% [ 33 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%